Kepuasan Pasien terhadap Komunikasi Dokter Pasien di Puskesmas - Dewi, Arlina (Universitas Muhammadiyah Yogyakarta, 2009)
Doctor patient communication is the important basis of diagnosis, therapy and preventive process. In a few cases in Primary, Care, most of doctrs do wrong diagnosis because of inhibition in communication. In a busy doctor practice, communication takes short time. Patient are dissatisfied to doctor care because of less attention and opportunity to express their feeling. The objective of this study is to determine the correlation between patient satisfaction and duration of doctor patient communication in Community Health Centre. The research method used cross sectional design with analytic type. The collected data using satisfaction questionnaire that filled directly by respondent and direct observation by researcher to duration of doctor patient communication. Sixty-four respondents selected at random from eight Community Health Centres in Primary Care where doctor care the patient. Spearman Correlation test is used to analyze the data. The study finds out that the duration of doctor patient communication is 2,96Â±1,27 minutes on average. Based on eight categories (greeting, non verbal, empathy, language, listening, giving information, summarizing, motivation) of patient satisfaction level, the highest score is empathy and the lowest score is greeting. Patient satisfaction score to female doctor is higher than male (p=0,026). There is moderate correlation (r=0,444, p0,005) between patient satisfaction and duration of doctor patient communication in Community Health Centre. In conclusion, there is moderate correlation between patient satisfaction and duration of doctor patient communication in Community Health Centre.Komunikasi dokter pasien merupakan landasan yang penting dalam proses diagnosis, terapi maupun pencegahan penyakit. Dalam beberapa kasus di Primary Care banyak dijumpai dokter yang keliru mendiagnosis karena adanya hambatan dalam komunikasi. Pada praktik dokter yang sibuk komunikasi yang terjadi hanya sangat singkat. Ketidakpuasan sebagian pasien terhadap layanan dokter karena merasa kurang diperhatikan dan tidak ada kesempatan dalam mengungkapkan perasaannya. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara kepuasan pasien dengan durasi komunikasi dokter pasien di Puskesmas. Metode penelitian menggunakan rancangan cross sectional dengan jenis penelitian analitik. Pengumpulan data menggunakan kuisioner kepuasan yang diisi langsung oleh responden dan observasi langsung oleh peneliti terhadap durasi komunikasi dokter pasien. Enampuluh empat responden pasien terpilih secara acak dari delapan Puskesmas tempat dokter Primary Care memberikan pelayanan. Analisis data menggunakan uji Spearman Correlation. Hasil penelitian didapatkan rata rata durasi komunikasi dokter pasien 2,96Â±1,27 menit. Dari delapan komponen kategori (greeting, non verbal, empathy, language, listening, giving information, summarizing, motivation) tingkat kepuasan pasien yang tertinggi pada empathy dan yang terendah pada greeting. Skor kepuasan pasien terhadap dokter perempuan lebih tinggi daripada dokter laki laki (p= 0,026). Terdapat korelasi sedang (r = 0,444, p0,005) antara kepuasan pasien dengan komunikasi dokter pasien di Puskesmas. Dari hasil tersebut dapat disimpulkan bahwa terdapat hubungan sedang antara kepuasan pasien dengan komunikasi dokter pasien di Puskesmas.